QTL mapping of yield components and kernel traits in wheat cultivars TAM 112 and Duster - Wang, Zhen; Dhakal, Smit; Cerit, Mustafa; Wang, Shichen; Rauf, Yahya; Yu, Shuhao; Maulana, Frank; Huang, Wangqi; Anderson, Joshua D.; Ma, Xue-Feng; Rudd, Jackie C.; Ibrahim, Amir M. H.; et al. (Frontiers in Plant Science, 2022)
In the Southern Great Plains, wheat cultivars have been selected for a combination of outstanding yield performance and drought tolerance as a long-term major breeding goal. To dissect the quantitative trait loci (QTL) for these traits, we conducted QTL mapping using 5,081 single nucleotide polymorphisms (SNPs) generated by genotyping-by-sequencing (GBS) for a population of 182 recombined inbred lines (RILs) derived from ‘TAM 112’ × ‘Duster’. A total of 30 pleiotropic QTL regions and 21 consistent QTL regions with 10 in common for 18 traits related to yield, agronomy, and kernel traits were identified from 13 irrigated and dryland environments. Three pleiotropic QTL on the short arms of chromosomes 2B (57.5 – 61.6 Mbps), 2D (37.1 – 38.7 Mbps), and 7D (66.0 – 69.2 Mbps) colocalized with genes Ppd-B1, Ppd-D1, and FT-D1, respectively. And four consistent QTL associated with kernel length (KLEN), thousand kernel weight (TKW), plot grain yield (YLD), and kernel spike-1 (KPS) (Qklen.tamu.1A.325, Qtkw.tamu.2B.137, Qyld.tamu.2D.3, and Qkps.tamu.6A.113) explained more than 5% of the phenotypic variation. QTL Qklen.tamu.1A.325 is a novel QTL with consistent effects under all tested environments. Marker haplotype analysis indicated the QTL combinations significantly increased yield and related traits. QTL and the linked markers identified in this study will facilitate future marker-assisted selection (MAS) for pyramiding the favorable alleles and map-based cloning some of these QTL.